Need to Assess Organic Carbon Pool in Soils: A Review - Iqbal, Sheikh; Tiwari, Subhash Chandra (Indian Forester, 2014)
The estimation of organic carbon pool in soils and their variability in different terrestrial ecosystems are essential to better understand the global C cycle, to estimate the soil C sink capacity, and to quantify the amount of SOC sequestered in a defined time period. The amount of C stored in the soil per unit area is highly variable as the magnitude of SOC pool at a location depends on a range of factors such as soil type, land use land cover and climatic conditions. These factors differ among different land use and land cover and affects the soil carbon storage. Consequently, several approaches and new techniques are needed to develop a reliable estimate of SOC pool at different scales and ecoregions. Therefore, there is a need to quantify and understand the storage and dynamics of SOC pool under different land use land cover to identify and discuss the better land use land cover adaptation options that could enhance SOC stocks in different locations and ecoregions to combat climate change, soil quality improvement and food security and subsequently to enhance the ecosystem services.